Modelling and control of base plate loading subsystem for the motorized adjustable vertical platform - Norsahperi, Nor Mohd Haziq; Ahmad, Salmiah; Fuad, A.F.M.; Mahmood, Iskandar Al Thani; Toha, Siti Fauziah; Akmeliawati, Rini; Darsivan, Fadly Jashi (IOP, 2017)
Malaysia National Space Agency, ANGKASA is an organization that intensively undergoes many researches especially on space. On 2011, ANGKASA had built Satellite Assembly, Integration and Test Centre (AITC) for spacecraft development and test. Satellite will undergo numerous tests and one of it is Thermal test in Thermal Vacuum Chamber (TVC). In fact, TVC is located in cleanroom and on a platform. The only available facilities for loading and unloading the satellite is overhead crane. By utilizing the overhead crane can jeopardize the safety of the satellite. Therefore, Motorized vertical platform (MAVeP) for transferring the satellite into the TVC with capability to operate under cleanroom condition and limited space is proposed to facilitate the test. MAVeP is the combination of several mechanisms to produce horizontal and vertical motions with the ability to transfer the satellite from loading bay into TVC. The integration of both motions to elevate and transfer heavy loads with high precision capability will deliver major contributions in various industries such as aerospace and automotive. Base plate subsystem is capable to translate the horizontal motion by converting the angular motion from motor to linear motion by using rack and pinion mechanism. Generally a system can be modelled by performing physical modelling from schematic diagram or through system identification techniques. Both techniques are time consuming and required comprehensive understanding about the system, which may expose to error prone especially for complex mechanism. Therefore, a 3D virtual modelling technique has been implemented to represent the system in real world environment i.e. gravity to simulate control performance. The main purpose of this technique is to provide better model to analyse the system performance and capable to evaluate the dynamic behaviour of the system with visualization of the system performance, where a 3D prototype was designed and assembled in Solidworks. From the Solidwork, the model was translated to Simmechanics with the system coordinate and specification i.e mass and inertia and actuator model was designed by using Simpower for simulating the system. Then, the system was integrated with controller by using conventional Proportional-Derivative (PD) controller with 0% steady state error, (ess) and 22.4% overshoot, (P.O) as the results.